Utilization of pumice powder and glass microspheres in cement mortar using paste replacement methodology - Kabay, Nihat; Miyan, Nausad; Ozkan, Hakan (ELSEVIER SCI LTD, 2021)
The effective use of pumice powder (PP) and glass microspheres (GM) as filler in cement mortar was investigated utilizing the paste replacement methodology (PRM). The PP and GM replaced the cement paste by 0%, 10%, and 20% by volume and several tests were conducted to determine the fresh and hardened properties. Test results indicate that the PRM method gives promising results in maintaining the compressive strength and reducing the voids content and water absorption compared to the reference (Ref) mix. Microstructural analysis revealed that the PP, compared to GM, provides an additional contribution to the researched parameters by densifying the matrix with reduced portlandite, reduced porosity and provided comparable compressive strength with the Ref mix at all test ages. The GM-modified composite yielded higher MIP-porosity but the pore structure of the matrix was modified and represented lower values for both the critical and the average pore sizes. The PRM enabled up to 20% replacement of the PP and GM and reduced the cement content accordingly without compromising the compressive strength and even improving the physical properties. (C) 2021 Elsevier Ltd. All rights reserved.
Keywords: Pumice powder; Glass microsphere; Microstructure; Physical properties; Mechanical properties; Construction & Building Technology; Engineering; Materials Science